Sinking in Premature Deindustrialisation or Revitalising Industrialisation? Nepal’s Prospective - Dahal, Madhav Prasad (Economic Journal of Development Issues, 2018)
Economies of the world in general evolve by transferring them from agriculture to manufacturing and then from manufacturing to services. Today’s most developed economies have experienced their deindustrialisation at higher level of per capita income. But developing countries have begun to fall in premature deindustrialisation at low level of per capita income which is not taken as a good sign for their overall economic development. This paper analyses the potentiality of premature deindustrialisation in the context of Nepal covering the data of the period 1975-2016. The issue of premature deindustrialisation is analysed in terms of the share of manufacturing output in the gross domestic product of the country and employment. There is evidence of premature deindustrialisation in Nepal. The paper argues that reindustrialisation is essential and possible in Nepal. Economic Journal of Development Issues Vol. 23&24 No. 1-2, (2017) Combined Issue, Page : 35-70